Diagnostic utility of endoscopic brush cytology in upper gastrointestinal malignancies. Issue 3 (4th December 2020) - Bhutani, Namita; Kumar, Raj; Arora, Sunil; Poswal, Pooja; Singla, Sham
Abstract: Introduction: The advent of endoscopy and endoscopic biopsy has greatly facilitated the detection and diagnosis of gastrointestinal neoplasms. Brush cytology often complements and increases the sensitivity and specificity of detection of GIT lesions in many ways. Materials and Methods: The present prospective study was conducted in the Department of Pathology in collaboration with Department of Gastroenterology at S.G.T. Medical College and University, Gurugram. A total of 50 patients suspected of having upper gastrointestinal malignancies formed the study group. After taking the detailed history, patients were subjected to endoscopy using flexible video endoscope. After brushing, biopsies were taken from the lesions and preserved in 10% formalin. The aim of the study was to evaluate the utility of endoscopic brush cytology in diagnosing upper gastrointestinal malignancies and its comparison with endoscopic biopsy. Results: In the present study, a total of 50 cases constituted the study group, during the period of 2018‐2019, with the age of patients ranging from 30 to 85 years. Mean age at presentation was 58 years. The most frequent age group affected was 41‐60 (44%) and most of them were men (66%). The sensitivity and positive predictive value in our study is 84.4% and 97.4%, respectively, while the specificity and negative predictive value is 100% and 50%, respectively. Conclusion: To conclude, brush cytology is a reliable, simple, safe, rapid, noninvasive yet effective, and inexpensive method of detecting malignancy of upper gastrointestinal tract.